La ausencia de una normativa en el código de la niñez y adolescencia que suspenda el pago de las pensiones alimenticias, afecta el derecho del alimentante cuando retoma la convivencia familiar - Escobar Sánchez, Klever Paúl (2014)
The family performs functions related to the duties of affection, to the transmission of patterns of behavior from parents to their children, and socialization in compliance with the rules. It also adds a direct function of monetary policy which is to transfer resources from parents to children, so that the latter acquire the skills for the development of his life. This includes housing, health, clothing, education and recreation. This is the right to food; with the right companies enforce the obligations of contribution among members of a family. Clearly mention that this duty is fulfilled often spontaneously, but by associating it with a couple of breaks leaves sometimes spontaneously fulfilled and it is necessary to enforce it. To date, the claims by way of a monthly pension under the sponsorship makes a lawyer and according to the discretion of the judge regarding the amount to be allocated and the precedent that the decisions they took after argued that the parent responsible for many problems and ended up paying the amount you wanted and willingly when he thought fit in accordance with their convenience. It is argued that if you do not have enough money or did not work, just the child through his mother did not receive any money or received, was a small amount. Importantly, the father was the only family responded to this legal requirement. Now all the claims are made without the sponsorship of a lawyer and only sufficient filing of a form with all information necessary to initiate the cause. After a maximum period of two days, the judge shall fix a minimum amount of pension (to settle) and a matter of immediate payment, regardless of the launched process. In addition, the final decision would be taken in a single hearing in the short term, but the solution would be monitoring the speed and that those on the different cases without prejudice to eat as much food. The problem arises by noting that there is a loophole in the Code of Children and Adolescents, which directly affects the right of the obligor as to demand a suspension of payment of alimony, since it has been found by legal means he has re-their family role and lives under one roof, leading to comply with all obligations to their fed, meaning economic, moral and social compliance absolutely, exercise maintenance in all aspects, then you can bad law require follow canceling alimony and the child's mother despite not having the child in their total support, continues to gather the food benefits, having a negative effect because that money should be invested in the child's or adolescent's no for other purposes other; the problem lies in the legal part is not the food suspended payment, risking further than what the obligor have performed a liquidation of alimony due and need to cancel or stop you simply as a measure for non-payment product a ballot of staff urgently. If it is true, in the event that the defendant has not paid child support by court order imposed by the fact of having entered a living again with the child's mother; or that defendant and protecting the obligor is found lower due to the mother for any circumstances be stopped. Mal we can issue simplistic criteria as to say that no matter who has the child, if the court imposed foods must pay or should be deprived of freedom until you cancel, this necessarily results from the lack of standards to which we refer, for oriented and fairly in allowing the judge to issue a right-adjusted and unadjusted resolution to reality. It is therefore important and necessary to consider rules in the Code of Children and Adolescents to suspend alimony as long as the bond between the obligor and the beneficiary and not cause any economic damage and even parento thereby improve the relations between father affiliates and son (s) that has often been the cause of family discord as grounds that it may be possible that in addition to provide protection and care for your child is paying alimony, whose mother charged money without reaching the child or teenager.